DESIGN OF LEATHER FRINGE BAG THROUGH THE IMPLEMENTATION OF BALI GRINGSING WOVEN FABRIC - Mutiana Pramita sari; Prima Yustana (Institut Seni Indonesia Surakarta, 2021)
Indonesia has an extraordinary wealth of cultural arts, one of which is the Gringsing woven fabric in Bali. The beauty of Gringsing weaving attracts the author to apply it to bag products as an aesthetic element. This design aims to design a women's bag with a fringe model through a combination of Grinsing weaving elements. This design uses the method of creation, namely: exploration, design, and realization stages. In addition, the design also pays attention to the approach to practical functions, themes/styles, ergonomics, and aesthetics. This design resulted in five designs of women's bags with fringe bag models with the application of Gringsing woven fabric, namely fringe tote bags, fringe slingbags, fringe backpacks, fringe handbags, and fringe waist bags. Of the five designs, two designs were realized into women's bag products, namely the fringe sling bag and backpack models. Through the design of creative bags that use motifs on Gringsing woven fabrics, can produce unique and distinctive typical creations that reflect Indonesian culture.